An ecological case-study of the benefits and challenges of socially-just leadership engaging in 'challenging conversations' about social disharmony. (1st October 2020) - Walsh, Lucas; Keddie, Amanda; Wilkinson, Jane; Howie, Luke
ABSTRACT: As sites of human social activity, schools must engage in challenging conversations between staff, students and their communities about social disharmonies. This paper presents interview data from a case study of Eucalyptus High School (not its real name), a large multicultural school located in a middle-class area in suburban Victoria (Australia). The paper examines the school's engagement in 'challenging conversations' about socially and politically volatile issues as part of a holistic approach to building school culture, highlighting certain limitations in this approach. An 'ecologies of practice' model is used to critically explore these, which could be used to support schools to adopt a broad and critical examination of the possibilities and limits of their cultivation of inclusive and nurturing environments.